Slavic Feminism and Female Portrait Genre in the Magazine Yugoslav Woman (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The topic of this paper is the female portrait genre in the magazine Yugoslav Woman, which was published from 1917 to 1920 in Zagreb. Its editor-in-chief, Slovenian writer Zofka Kveder, turned the magazine into a hub for building a network of distinguished women from different Slavic countries. Together with magazine contributors, she published biographies, as well as literary reviews of the works of Slavic women writers. Thus, they played a part in developing the idea of Slavic feminism and Slavic women’s literary history. Portraits were written about women writers, as well as women in science, historical figures, humanitarian workers and artists. Therefore, aside from transcending state borders, the magazine has both a diachronic and synchronic character, since the texts were dedicated to notable women throughout history and their counterparts at the time.
Keywords: Zofka Kveder; Yugoslav Woman; female portrait; Slavic feminism; biography